Model-based approach for maize yield gap analysis related to climate variability and nitrogen management - Andréa, Maria Carolina da Silva (2016)
To achieve food security and meet environmental requirements, the average rates of major crop yields in crops such as maize are expected to increase instead of expansion of cultivated areas. Maize crop has as main factors responsible for the low yields in Brazil the water and nitrogen (N) deficits. The concept of yield gaps is the difference between the maximum yield that can be achieved in a given place, limited by water (Yw) or not (Yp), and the average yields, observed under practical conditions (Ya). This concept is of great importance for characterizing the range of maximum yields and definemanagement strategies to its mitigation. Yield potential (Yp) is determined by conditions of temperature, solar radiation, photoperiod and genetic potential; to Water-limited yield (Yw) is added the water limitation imposed by crops on rainfed condition. In this study we aimed to characterize the variability of yield gaps related to environmental and management conditions; and to evaluate the economic and energy returns related to management of these yield gaps through the mechanical application of nitrogen fertilizer in six regions located in the South Central portion of the country in two periods of maize cultivation (1st and 2nd maize growing seasons). Yield gaps related to water restriction (CYg = Yp - Yw) and imposed by management conditions (MYg = Yw - Ya) were determined through aid of integrated models DSSAT system (Decision Suport System for Agrotechnology Transfer). The maize model (CSM CERES-MAIZE) was calibrated with cultivars trial data obtained for the last few years in all evaluated regions. In the 1st growing season, Yp was higher and Yw was higher and more variable than on 2nd growing season due to climate variability. The yield gaps relative to management were more limiting than the gaps relative to water deficit in almost all the evaluated regions. In both crops\' growing seasons, higher and lower MYg were found in two regions of Southern and Midwestern portion of the country, respectively. Although both regions presented high average yields (Ya), different environmental conditions determined the largest absolute differences between their rates of Yp, Yw and MYg. When assessing the profitability (R$ k g-1, MJ kg-1, R $ ha-1; MJ ha-1) of N application as MYg reduction strategy, the behavior of the variation in yields with increasing rate of N was observed. In general, the diminishing returns showed higher use efficiency (per harvested yield and per unit area) at lower N rates (20-80 kg ha-1). Economic and energy profits (regardless of their rate of change related to the increased application of cost) were found at higher N rates (90-400 kg ha-1), and this limit is directly influenced by local climate conditions. Local management of MYg can be more or less viable depending on the combination of environmental conditions and usual management conditions. In general, the cost of N application is higher in 2nd growing season due to most limiting climatic conditions, but regions with efficient management of yield gapswere alsofound in 2nd growing season